A reflection on agricultural land tax in Zimbabwe: paper presented at a conference held on the 14th-16th July 2015, Elephant Hills Resort, Victoria Fallls, Zimbabwe - Chigome, Joyce (Midlands State University, 2016)
Theme:1st International Research Conference On Driving Socio-Economic Development Through Value Addition And Sustainable Use Of Resources. Sub Theme: Water resources management, climate change, food security and sustainable development